Stuttering Patterns of a Stand-up Comedian with Speech Impairment: A Case Study of Nina G’s Utterances - Yolanda Marcela Binambuni; Nina Setyaningsih (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
A stand-up comedian needs to have good communication skills and ability to deliver material in a humorous way. This becomes a challenge for a comedian that has speech impairment, one of whom is Nina G, the stuttering comedian. Wingate (in Bloodstein, et.al, 2021) argues that stuttering is characterized by involuntary repetitions or prolongations in the utterance of short speech elements that occur frequently and are not readily controllable. These characteristics are also observable in her speech. This research is aimed at investigating the features of stutters in Nina G’s speech, specifically in terms of the linguistic elements such as syntactic (phrases), lexical (words), phonetic (sounds) elements of the stutter. The data were taken from Nina G’s performances uploaded on YouTube, and a descriptive qualitative method was used to analyze the data. The results of the preliminary analysis reveal that the most dominant characteristic is sound repetition (48.3%) which occurs in common nouns (43.4%) and when the initial sound begins with [s] (39.16%). The next is word repetition (17.6%) which frequently occurs in simple preposition and simple conjunction, followed by prolongation (12.3%) which occurs in common noun and the sound [ɪ] (13.62%). Then, syllable repetition (11.9%) happens most when she utters lexical verbs and initial syllable beginning with [s] (23.52%). The rest are phrase repetition (4.7%) that occurs in adverb and simple preposition, and block (5.2%) which mostly appears in lexical verb. Thus, it can be concluded that Nina G’s speech demonstrates certain patterns of stutter characteristics. Furthermore, it is also found that the situations she is in do not affect her stuttering characteristics at all. This research also suggests that despite her speech impediment, Nina G still succeeds in communicating her ideas and delivering jokes in her stand-up comedy performances.